Factores de riesgos que influyen en la preeclampsia en mujeres gestantes de 15-20 años, Sub Centro de Salud Ahuano, ciudad de Tena, Provincia Napo, octubre 2018 – abril 2019 - Alcivar Sigua, Katherine Stephanie (2019)
Preeclampsia is a disease that develops its clinical stage in pregnant women after 20 weeks of pregnancy being one of the main causes of complications during pregnancy such as: previous detachment of placenta and in the newborn prematurity, intrauterine growth restriction or maternal and neonatal death. The purpose of this study is to serve the community as an aid, it is relevant for the health personnel, because they are the ones who take care of the health of the population, and of the well-being of the pregnant adolescents, by recognizing the possible risk factors that lead to a preeclampsia; providing immediate attention in cases of complications. The objective of this project is to: Determine the risk factors that influence the appearance of preeclampsia in pregnant women from 15 to 20 years of age who come to the Ahuano sub health center belonging to the City of Tena, Napo Province in the period October 2018- April 2019. In the study methodology, the inductive method was applied with the modality of qualitative and quantitative research, type of descriptive research. The results were obtained with the application of surveys and closed questions and with the help of the SPSS program on a sample of the representative group. The results obtained in the sample of studies differentiates that the main risk factors are: the prenatal controls because we observed through the surveys that 41% of the pregnant women go meanwhile with 58% of the pregnant women do not go to their controls. It is evident with 71% that they live far from the health house, for that reason it is difficult for them to attend. Also with 70% for their economic level they are affected to go to their controls. It is observed that the pregnant women have ignorance of 76% that is to say they do not know of the subject. There have been 59% of pregnant women with home visits and with 52% consuming alcohol during their pregnancy.